2019
DOI: 10.1016/j.cemconcomp.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Low clinker high performance concretes and their potential in CFRP-prestressed structural elements

Abstract: Three novel low-clinker-high-performance concretes (LCHPC) with clinker replacement levels of 54, 58 and 70 % were developed to substitute high-performance concrete (HPC) in carbon-fiber-reinforcedpolymer (CFRP) prestressed structural elements. The clinker substitution was achieved by a high amount of limestone filler and smaller amounts of metakaolin and silica fume. After 28 days, the LCHPCs reached high compressive strength values, between 77 MPa and 88 MPa, and Young's moduli between 35 GPa and 44 GPa. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 51 publications
3
20
0
1
Order By: Relevance
“…New materials for prestressing of structural concrete elements, UHM-CFRP and LCHPCs introduced in 2016 [3] and 2019 [6] respectively, were tested to observe their behaviour during prestressing and during 4-point bending tests of such elements. In addition, the structural behaviour of these beams was further characterized.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…New materials for prestressing of structural concrete elements, UHM-CFRP and LCHPCs introduced in 2016 [3] and 2019 [6] respectively, were tested to observe their behaviour during prestressing and during 4-point bending tests of such elements. In addition, the structural behaviour of these beams was further characterized.…”
Section: Methodsmentioning
confidence: 99%
“…This concrete recipe with a water to binder ratio (w/b) of 0.35, named C1, contained 443.0 kg/m 3 of ordinary Portland cement CEM I 52.5 R, 120.0 kg/m 3 fly ash, 20.0 kg/m 3 silica fume, 1107 kg/m 3 sand 0/4, 487 kg/ m 3 gravel 4/8 and 5.2 kg/m 3 superplasticizer (SP). This is the same recipe that was recently employed as a reference mix during the development of LCHPCs [6], based on a HPC used by the Swiss precast industry in CFRP prestressed structural elements [36]. In addition, to evaluate the potential of LCHPCs for prestressing applications, the recipe C4 (w/b = 0.17) was chosen from three recently developed LCHPCs [6].…”
Section: Raw Materials and Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, excessive amount of energy need during production and causing high CO2 emission are among its disadvantages. Researchers state that it is responsible for 5-7% of the world's CO2, with around 0.66-0.82 kg CO2 emission per 1 kg of PC (Lämmlein et al, 2019;Peng et al, 2012;Xie et al, 2019;Zhang et al, 2018Zhang et al, , 2020 On the other hand, thanks to geopolymer material technology, it has been revealed that greenhouse gas emissions and energy consumption were reduced by 73% and 43%, respectively (Meyer, 2009). This makes it attractive to investigate geopolymer binders as an alternative binder instead of Portland cement in concrete production (Juenger et al, 2011).…”
Section: Introductionmentioning
confidence: 99%